Aerospace series. Steel X3CrNiMoAl (1.4534). Vacuum induction melted and consumable electrode remelted. Solution treated and precipitation treated. Bars for machining. a or D ≤ 200 mm. 1 200 MPa ≤ Rm ≤ 1 350 MPa. (17th January 2023) - British Standards Institution,
No abstract available